2021
DOI: 10.3390/cancers13143609
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α May Exert Different Antitumor Effects in Response to Radioactive Iodine Therapy in Papillary Thyroid Cancer with/without Autoimmune Thyroiditis

Abstract: Autoimmune thyroiditis (AIT) may impair radioiodine (131I) uptake in papillary thyroid cancer (PTC). Finding the mechanisms that govern immune cells during 131I therapy of PTC with concomitant AIT (PTC + AIT) could provide a rationale. Our study aimed to evaluate the effects of 131I on anti-thyroglobulin antibodies (TgAb), matrix metalloproteinase-9 (MMP-9) and its tissue inhibitor TIMP-1 and tumor necrosis factor-α (TNF-α) and its receptors TNFR1 and TNFR2, in PTC and PTC + AIT patients. Peripheral blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Furthermore, the application of 131 I evokes thyroid cancer cell immobilization, which conforms to a previous study that found that the administration of 131 I represses thyroid cancer cell migration by modulating NIS expression and location (37). Moreover, the administration of 131 I upregulates the secretion of tumor necrosis factor-a (TNF-a) and its receptors TNFR1 and TNFR2 to initiate anti-tumor effects (38).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the application of 131 I evokes thyroid cancer cell immobilization, which conforms to a previous study that found that the administration of 131 I represses thyroid cancer cell migration by modulating NIS expression and location (37). Moreover, the administration of 131 I upregulates the secretion of tumor necrosis factor-a (TNF-a) and its receptors TNFR1 and TNFR2 to initiate anti-tumor effects (38).…”
Section: Discussionsupporting
confidence: 87%
“…The presence of direct correlations between autoimmune thyroiditis and the presence of repairable and nonrepairable dislocations of one of the joints may be associated with the activation of MMP expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…The association of DTC with T2DM has led to a change in the tumor microenvironment [25]. The tumor microenvironment confers ionizing radiation with either immunosuppressive or immune-stimulating properties [10,26]. There is still a lack of information on the role and functionality of immune cells after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Blood cell interactions are essential in the pathophysiology of inflammation and immune responses in DTC patients [10]. These interactions have many facets, and it is often difficult to distinguish the specific roles of each cell type in response to high cumulative doses of 131 I.…”
Section: Introductionmentioning
confidence: 99%